Elaboración de un folleto ilustrado para fomentar la cultura y tradición de las fiestas del príncipe San Miguel, patrono del cantón Salcedo provincia de Cotopaxi durante el periodo 2016 - Peralta Cárdenas, Diana Carolina (2016)
The reason of this project is a source of support to strengthen information of the history and religion of “Principe San Miguel”, since this was a historical and transcendental event. As they mark the first celebration, they did it with Mr. Juan Clavijo, who chose on September 29, 1573 to found the town of “San Miguel de Molleambato”. The most important of this celebration is the Eucharist, there, the votary are grateful to Principe San Miguel for the favors granted, further in this celebrated known rites are performed, such as sung mass, to this ceremony assist priests from different parts, this Eucharist go on for two hour. The project to be developed with the purpose to make known this tradition., while encouraging the citizenry to appreciate the importance of this representative icon by a digital and print support as well as promote awareness of this historical figure, at the same time while promoting religious values in the inhabitants to have notion of who was el “Principe San Miguel”. Making of an illustrated booklet helps identify the characters that make up this religious festival. We as designers arises a creative and innovative proposal, to share the history with the rest of the community.